Comparison of three methods of EPR retrospective dosimetry in watch glass - Marciniak, Agnieszka; Juniewicz, Małgorzata; Ciesielski, Bartłomiej; Prawdzik-Dampc, Anita; Karczewski, Jakub (Frontiers in Public Health, 2022)
In this article we present results of our follow-up studies of samples of watch glass obtained and examined within a framework of international intercomparison dosimetry project RENEB ILC 2021. We present three methods of dose reconstruction based on EPR measurements of these samples: calibration method (CM), added dose method (ADM) and added dose&heating method (ADHM). The study showed that the three methods of dose reconstruction gave reliable and similar results in 0.5–6.0 Gy dose range, with accuracy better than 10%. The ADHM is the only one applicable in a real scenario, when sample-specific background spectrum is not available; therefore, a positive verification of this method is important for future use of EPR dosimetry in glass in potential radiation accidents.